The bug in teacher's coffee and other school poems - Dakos, Kalli; Reed, Mike, 1951- (New York : HarperCollins, 1999)
A collection of simple poems depict the activities at school from the morning welcome until the closing bell.
Keywords: Education, Elementary -- Juvenile poetry; Elementary schools -- Juvenile poetry; Children's poetry, American; Schools -- Poetry; American poetry